2012
DOI: 10.1007/s10953-012-9812-9
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity Arrhenius Activation Energy and Derived Partial Molar Properties in 1,4-Dioxane + Water Binary Mixtures from 293.15 to 323.15 K

Abstract: The knowledge and prediction of physicochemical properties of binary liquid mixtures is of great importance for understanding intermolecular interactions. Viscosities (η) have been investigated by using density (ρ) and kinematic viscosity (ν) measurements for 1,4-dioxane + water (D-W) mixtures over the entire range of mole fractions under atmospheric pressure, at 311.15, 316.15 and 320.15 K, in order to increase the studied temperatures range available from the literature and to improve the investigations. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
61
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 35 publications
8
61
0
Order By: Relevance
“…The A s -values are very close to the shear viscosity of the same system in its vapour-phase at the same pressure and at the normal boiling temperature [20][21][22][23][24][25][26][27]. Thus the high A s -value of DMF, imply that the shear viscosity of DMF at vapour phase is nearly about ten times than of EtOH and it is also concluded that EtOH molecules bounding are more random and disordered in vapour state.…”
Section: Temperature-dependence Of Liquid Shear Viscositysupporting
confidence: 54%
See 4 more Smart Citations
“…The A s -values are very close to the shear viscosity of the same system in its vapour-phase at the same pressure and at the normal boiling temperature [20][21][22][23][24][25][26][27]. Thus the high A s -value of DMF, imply that the shear viscosity of DMF at vapour phase is nearly about ten times than of EtOH and it is also concluded that EtOH molecules bounding are more random and disordered in vapour state.…”
Section: Temperature-dependence Of Liquid Shear Viscositysupporting
confidence: 54%
“…In the same context, the variation of the activation energy E a versus the molar composition (x 1 ) can give evidence of eventual change or modification in the complex structure or clusters [20] [ formed in binary fluid systems under effect of temperature and/or mixture composition [20][21][22][23][24][25][26][27]. When the activation energy Ea for the full mole compositions in the studied fluid system is depicted in Fig.…”
Section: Temperature-dependence Of Liquid Shear Viscositymentioning
confidence: 96%
See 3 more Smart Citations